2013
DOI: 10.1007/s00394-013-0576-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of submicron fat droplets in a drink on satiety, food intake, and cholecystokinin in healthy volunteers

Abstract: When this particular fat at these amounts is delivered in a meal replacement drink, droplet size does not influence appetite or food intake. This effect is independent of the amount of fat or plasma cholecystokinin changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The evidence in support of fish oil and SPL is equivocal at best, with a majority of the research indicating no benefit of SPL (Y. K. Chan et al 2017;Peters et al 2014), despite earlier studies suggesting otherwise (Burns et al 2001(Burns et al , 2000(Burns et al , 2002. In one study, fractionated oat oil was shown to increase satiety and the circulating concentration of satiety hormones (Ohlsson et al 2014), and so more data is required to support these initial positive findings.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence in support of fish oil and SPL is equivocal at best, with a majority of the research indicating no benefit of SPL (Y. K. Chan et al 2017;Peters et al 2014), despite earlier studies suggesting otherwise (Burns et al 2001(Burns et al , 2000(Burns et al , 2002. In one study, fractionated oat oil was shown to increase satiety and the circulating concentration of satiety hormones (Ohlsson et al 2014), and so more data is required to support these initial positive findings.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…This may explain the larger effect seen in postprandial concentrations of CCK, PYY, and GLP-1 with LOO compared to Fabuless TM , but further study is required to confirm this. Peters et al (2014) reported no effect of droplet size when administered in a meal-replacement drink, and they discuss the potential for the background effect of the drink (which contained 10g of protein in the 606 kJ drink) which may have decreased sensitivity to the lipids added. This is in spite of the fact that lipolysis was significantly higher in the smaller droplet (0.1 μm) compared to the larger droplet (3 μm).…”
Section: Acute Intake Of Small Particle Lipids On Satietymentioning
confidence: 99%
“…For example, a considerably greater rate of lipolysis (and therefore plasma triglyceride concentration and CCK release) is observed with smaller oil droplet sizes, due to the greater interfacial area available for digestive lipase binding. This behaviour has been observed within in vitro (Armand et al, 1992;Peters et al, 2014) and in vivo studies (Armand et al, 1999;Borel et al, 1994;Maljaars et al, 2012;Peters et al, 2014;Seimon et al, 2009). In addition, the size of oil droplets directly infused into the duodenum have been shown to have multiple effects on both gastric behaviour and satiety (Seimon et al, 2009): larger oil droplets infused directly into the duodenum were associated with less suppression of antral and duodenal pressure waves, reduced release of CCK and PYY, and lower suppression of rated hunger and actual food intake.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 64%
“…Previous research considering emulsion structures has predominantly considered gastro-intestinal structuring, in an attempt to achieve satiety via post-ingestive and post-absorptive mechanisms, with emulsion oil droplet size and emulsifier type being the two main properties investigated (Armand et al, 1999;Maljaars et al, 2012;Mun, Decker and McClements, 2007;Golding and Wooster, 2010;Lundin, Golding and Wooster, 2008;Peters et al, 2014;Seimon et al, 2009;Singh, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT pre-ingestive approaches (i.e. considering sensory mechanisms) has recently been considered and highlighted as potentially effective (Lett et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent human studies addressed short-term effects of LEs on eating behavior, including the effect of intragastric LE administration on plasma CCK (1619), active GLP-1 (17) and total PYY (19, 20). However, with oral ingestion of LEs mainly data for CCK are available (2022). The lack of longer-term studies assessing both changes in eating behavior and GI hormones in humans is largely due to the large costs of such studies (23), associated practical limitations and high inter-individual variations.…”
Section: Introductionmentioning
confidence: 99%